Well-maintained lawn enhances aesthetic beauty - Sindhu, S S; Singh, Babita (Indian Horticulture, 2019)
A lawn has a charm of its own. It enhances the beauty of a garden, be it large or small. It also complements the beauty of surrounding objects, whether they are trees, shrubs or flower beds. It is not difficult to draw out a lawn from the verandah and the windows of house should be free and uninterrupted. A spacious lawn may be provided with the beds of flowering plants. A group of shrubs or trees of attractive form or specimen shrubs or Thuja Oriental's or travelers palm or a large succulent may be planted here and there in pockets made in the lawn to form colonies of themselves and bear their beautiful flowers.